The accuracy of caries risk assessment in children attending South Australian School Dental Service: a longitudinal study. Issue 1 (29th January 2014) - Ha, Diep H; Spencer, A John; Slade, Gary D; Chartier, Andrew D
Abstract : Objectives: To determine the accuracy of the caries risk assessment system and performance of clinicians in their attempts to predict caries for children during routine practice. Design: Longitudinal study. Setting and participants: Data on caries risk assessment conducted by clinicians during routine practice while providing care for children in the South Australian School Dental Service (SA SDS) were collected from electronic patient records. Baseline data on caries experience, clinicians' ratings of caries risk status and child demographics were obtained for all SA SDS patients aged 5–15 years examined during 2002–2005. Outcome measure: Children's caries incidence rate, calculated using examination data after a follow-up period of 6–48 months from baseline, was used as the gold standard to compute the sensitivity (Se) and specificity (Sp) of clinicians' baseline ratings of caries risk. Multivariate binomial regression models were used to evaluate effects of children's baseline characteristics on Se and Sp. Results: A total of 133 clinicians rated caries risk status of 71 430 children during 2002–2005. The observed Se and Sp were 0.48 and 0.86, respectively (Se+Sp=1.34). Caries experience at baseline was the strongest factor influencing accuracy in multivariable regression model. Among children with no caries experience at baseline, overall accuracy (Se+Sp) was only 1.05, whereas it was 1.28 among children with at least one tooth surfaces with caries experience at baseline. Conclusions: Clinicians' accuracy in predicting caries risk during routine practice was similar to levels reported in research settings that simulated patient care. Accuracy was acceptable in children who had prior caries experience at the baseline examination, while it was poor among children with no caries experience.